Allocation des droits à bâtir et recours contentieux : quels registres d’argumentation portés par les riverains ? - Lisa Yahi; Daria Guiomard; Romain Melot; Yann Gérard (Métropoles)
Empirical data on planning disputes commonly adjudicated by the courts remain quite poor in the literature in social sciences. Based on a statistical study of a sample of some 300 cases in a local administrative court in the South of France, the inquiry underlines the need to consider local rulings that organize building rights beyond simple zoning concerns. Our study proposes an in-depth analysis of the lines of argument used by litigants. We distinguished between cases filed by the local State administration (acting as a guardian of legality) and those filed by residents in the neighborhood of contested developments.